Traditional Ritual to Cure Mental Illness According to Manggarai Culture in East Nusa Tenggara - Daulima, Novy Helena Catharina; Eka, Angelina (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2023)
Introduction: Mental illness treatment using traditional methods is still carried out in various regions in Indonesia, including in the Manggarai regency, East Nusa Tenggara. The aim of this study is to describe the types of traditional rituals performed to cure mental illness in Manggarai culture. Methods: This study uses an ethnographic approach which is supported by a qualitative descriptive approach. Data were collected by conducting in-depth interviews with 10 cultural leaders. Results: This study identified 4 types of rituals in treating mental illness namely peler rituals to cure mental illness due to being possessed by evil spirits, keti manuk neni rituals to cure mental illness due to heredity, Teing hang ritual heals mental illness due to ungratefulness to ancestors, and the oke dara ta'a ritual to heals mental illness due to having black magic. Conclusion: The results of the study indicate that there are still many people who practice traditional healing practices for people with mental illnesses and neglect medical treatment, resulting in relapses that lead to pasung or physical restraint and confinement of people with mental illnesses. Therefore, in providing education and promoting mental health in the community, it is necessary to emphasize the effectiveness of medical treatment.